Tuberculous endogenous endophthalmitis presenting acute anterior uveitis with hypopyon - M. Mejbahul Alam; Zahedur Rahman; Krishnakumar Subramanian; Parthopratim Dutta Majumder (Oman Journal of Ophthalmology)
A 27-year-old male with pain, redness, and vision loss in the right eye was diagnosed with acute anterior uveitis with hypopyon and treated with topical corticosteroid and cycloplegic eyedrops. Two weeks later, he developed severe vitritis. Then, after 1 month of oral corticosteroid treatment, his condition did not improve; therefore, he underwent pars plana vitrectomy with intravitreal antimicrobial injection in the right eye with suspicion of endogenous endophthalmitis. Polymerase chain reaction (PCR) from vitreous aspirate were negative for herpes viruses, eubacterial and panfungal genomes. After 3 months, the patient developed a painful blind eye and was eviscerated. Histopathology and PCR from ocular specimens confirmed the presence of Mycobacterium tuberculosis. High-resolution computed tomography chest showed calcific nodules in the upper lobe of the right lung, and the Mantoux test was positive. Further inquiry revealed that the patient’s father had pulmonary tuberculosis (TB) 4 years earlier. Ocular TB remains a great masquerader; the clinicians in the TB-endemic region must bear a high index of suspicion of TB while managing a case of endogenous endophthalmitis.